A hand-powered microfluidic system for portable and low-waste sample discretization. Issue 18 (13th August 2021) - Xie, Tengbao; Wang, Ping; Wu, Lei; Sun, Bangyong; Zhao, Qiang; Li, Gang
Abstract : A portable, disposable, and low-waste sample discretization system is presented for digital assays in resource-poor settings and point-of-care diagnostics. Abstract : In this work, we present a simple and equipment-free system for discretizing samples into tens of thousands of discrete volumes in tens of seconds. Unlike conventional sample discretization systems that require bulky syringe pumps, pressure controllers, or vacuum equipment, our system requires only a sheet of water-soluble film, a hand-operated syringe, and a microfluidic device containing a high-density microchamber array. In this system, the water-soluble film seals the device inlet to form a closed channel–chamber system, while the syringe is used to create a vacuum in the closed system. Benefitting from the high negative pressure created by syringe-vacuum and the dissolution-triggered gating mechanism of the sealing water-soluble film, the aqueous sample loaded into the device inlet can be rapidly partitioned into tens of thousands of isolated chambers without the need for any expensive pumping systems. We demonstrated the utility of this system by exploiting it for digital PCR. We believe that this simple discretization system will find broad applications, such as in digital bioassays, single-cell analysis, and point-of-care diagnostics.